2020
DOI: 10.1007/s10955-020-02663-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Chemical Reaction Systems with Detailed Balance Using Gradient Structures

Abstract: We consider various modeling levels for spatially homogeneous chemical reaction systems, namely the chemical master equation, the chemical Langevin dynamics, and the reaction-rate equation. Throughout we restrict our study to the case where the microscopic system satisfies the detailed-balance condition. The latter allows us to enrich the systems with a gradient structure, i.e. the evolution is given by a gradient-flow equation. We present the arising links between the associated gradient structures that are d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…The gradient‐flow classical structure for a driving functional U is 𝔾false(nfalse)truen˙=scriptDU0.1em; starting with Mielke, 28 provided there exists 𝕂false(nfalse)=𝔾1false(nfalse), the following formulation was proposed and successfully used into, e.g., 29–36 truen˙=𝕂false(nfalse)false[scriptDUfalse]0.1em, where the Onsager structure 𝕂 can be splitted additively into different contributions. For instance, in our case, we may set: 𝕂=𝕂D+𝕂R0.1em,0.30em𝕂Dfalse[0.1em·0.1emfalse]=divSfalse(nfalse)false[0.1em·0.1emfalse]0.1em,0.30em𝕂Rfalse[0.1em·0.1emfalse]=Hfalse[0.1em·0.1emfalse]0.1em. …”
Section: The Continuum Model For Isothermal and Rigid Scintillators: The Boundary Value Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The gradient‐flow classical structure for a driving functional U is 𝔾false(nfalse)truen˙=scriptDU0.1em; starting with Mielke, 28 provided there exists 𝕂false(nfalse)=𝔾1false(nfalse), the following formulation was proposed and successfully used into, e.g., 29–36 truen˙=𝕂false(nfalse)false[scriptDUfalse]0.1em, where the Onsager structure 𝕂 can be splitted additively into different contributions. For instance, in our case, we may set: 𝕂=𝕂D+𝕂R0.1em,0.30em𝕂Dfalse[0.1em·0.1emfalse]=divSfalse(nfalse)false[0.1em·0.1emfalse]0.1em,0.30em𝕂Rfalse[0.1em·0.1emfalse]=Hfalse[0.1em·0.1emfalse]0.1em. …”
Section: The Continuum Model For Isothermal and Rigid Scintillators: The Boundary Value Problemmentioning
confidence: 99%
“…In a series of recent papers, 32–36 dealing with the gradient structure of () it is shown that also () admits a gradient structure with 𝕂=𝕂R for detailed balanced recombination mechanisms and hence, the energy dissipation methods can be used with success to get asymptotic decay estimates.…”
Section: The Approximated Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given compactness and local equilibrium, the hydrodynamic limit of interacting particle systems is usually proven at the level of the stochastic process [KL99]. In this work, we take a different route and, still not aiming at a full rigorous proof, apply a heuristic method by Maas and Mielke that uses gradient structures [MM20]. These are geometric structures that were introduced in both physical [Grm85,Mor86] and mathematical [DGMT80,CV90] contexts to model dissipative phenomena, in particular in the literature of nonequilibrium thermodynamics [Ons31, G Ö97].…”
Section: Introductionmentioning
confidence: 99%
“…Already the analysis of the arising equations for the pair distribution is not fully covered by the existing PDE theory, it is also open whether it is more suitable to study the formulation with the pair distribution or rather the one with the conditional distribution. Also the analysis of gradient structures or generalizations at the level of the pair distribution is an interesting topic for further investigations, related to the evolution of gradient structures like in [13] and possibly with other structures as in [42] for discrete models. An even more challenging question is the analysis of pair closure relations for the BBGKY-type hierarchy, for which one would possibly need similar quantitative estimates as for the mean-field limit in [47,54], which currently seem out of reach.…”
mentioning
confidence: 99%